ILMU á¸¤Uá¸ÅªRÄª Khazanah Epistemologi Islam - Saidurrahman, Saidurrahman (TEOLOGIA, 2014)
Abstract: Knowledge of the presence (á¸¥uá¸Å«rÄ«) with mystical experience as describe above is deemed the most popular models of knowledge in Islamic philosophy at the same coloring methodology and epistemology of Islam. Through logical arguments, semantic analysis and epistemoÂlogy sharp SuhrawardÄ« considered very successfully demonstrate authenticity huduri science as a science model of non-representational. Among the classical epistemological problems that have not been resolved until now-but able to be dissected in clear and distinct- is about the relationship of subject and object of knowledge, that is the problem more acute in modern Western philosophy. What is interesting is when when to review the issues very carefully and consistently Mehdi directing and bringing the students (who interest in Islamic philosophy) into the recesses of the inner world and the dialogue with the depth of their own existence. It is undeniable that Hairi Mehdi Yazdi take existentialist philosophy illumination SuhrawardÄ« and Mulla á¹¢adrÄ as a main reference, as he learned the lesson of Plato, Aristotle, Plotinus, Ibn SÄ«nÄ, and al-á¹¬Å«sÄ«, citing the idea of ââa number of Western philosophers were actually familiar with the science huduri that he wanted to offer. However unique, he expertly directs their ideas to the conclusion that it is inevitable for us to acknowledge the existence of non-phenomenal knowledge. Abstrak: Pengetahuan dengan kehadiran (á¸¥uá¸Å«rÄ«) dibarengai pengalaman mistik seperti yang paprkan diatas dipandang model pengetahuan yang paling populer dalam filsafat Islam sekaligus mewarnai metodologi dan epistemologi Islam. Melalui argumen-argumen logis, analisis semantik dan epistemologi yang tajam SuhrawardÄ« dipandang sangat berhasil mendemonstrasikan keautentikan ilmu huduri sebagai sebuah model ilmu non-representasional. Diantara problem-problem klasik episteÂmologis yang belum terselesaikan hingga kiniâtetapi mampu dibedah secara clear dan distinkâadalah tentang hubungan subjek dan objek pengetahuan, yang problemnya makin akut dalam filsafat Barat modern. Yang menarik adalah ketika ketika mengulas masalah-masalah itu Mehdi sangat cermat dan konsisten mengarahkan dan membawa para murid-muridnya (peminat filsafat Islam) memasuki relung-relung dunia batin dan berdialog dengan kedalaman eksistensi mereka sendiri. Tak dapat dipungkiri bahwa Mehdi Haâiri Yazdi mengambil filsafat iluminasi SuhrawardÄ« dan eksistensialis Mulla á¹¢adrÄ sebagai acuan utamanya, seraya memetik pelajaran dari Plato, aristoteles, Plotinus, Ibn SÄ«nÄ, dan al-á¹¬Å«sÄ«, mengutip gagasan sejumlah filosof Barat yang sebetulnya asing dengan ilmu á¸¥uá¸Å«rÄ« yang hendak ia tawarkan. Akan tetapi uniknya, dengan piawai ia mengarahkan gagasan-gagasan mereka kepada penarikÂan kesimpulan bahwa adalah tak terelakkan bagi kita untuk mengakui eksistensi pengetahuan non-fenomenal itu. Keywords: ilmu á¸¥uá¸Å«rÄ«, khazanah, epistemology, cogito ergo sum, atheisme.